Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.12794/journals.ntjur.v1i1.74
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Emotional Abuse and Neglect in Adulthood

Abstract: Are neglected and maltreated children more likely to have homicidal tendencies? There are many studies thatshow how sexual abuse and physical abuse can lead to domestic and sexual violence as an adult but not manystudies have shown how verbal abuse or emotional maltreatment can lead to having homicidal tendencies. Inthis study I will show how emotional abuse can cause children to have cognitive deficits that prevent them frommaking correct, moral decisions in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Many studies have shown that these negative results are anxiety disorder, susceptibility to depression, suicidal tendencies, aggression, delinquency, antisocial behaviors, substance abuse, etc. (Balcı-Akpınar, Küçükoğlu, Ejder Apay, Karaca & Balcı, 2019;Brown, Cohen, Johnson & Smailes, 1999;Chapple et al, 2005;Frias-Armenta, 2002;Jimenez, 2019;Salokangas et al, 2020). Chapple et al (2005) concluded in their study that physical neglect, which is one of a traumatic type, causes individuals to be more aggressive in the later stages of life; as a result, these individuals are more likely to be excluded by their social environment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that these negative results are anxiety disorder, susceptibility to depression, suicidal tendencies, aggression, delinquency, antisocial behaviors, substance abuse, etc. (Balcı-Akpınar, Küçükoğlu, Ejder Apay, Karaca & Balcı, 2019;Brown, Cohen, Johnson & Smailes, 1999;Chapple et al, 2005;Frias-Armenta, 2002;Jimenez, 2019;Salokangas et al, 2020). Chapple et al (2005) concluded in their study that physical neglect, which is one of a traumatic type, causes individuals to be more aggressive in the later stages of life; as a result, these individuals are more likely to be excluded by their social environment.…”
Section: Discussionmentioning
confidence: 99%